Conflict Management Strategies in the Workplace for Harmonious and Productive Work Environment - Nuraini, Reny; Wulandari; Halizah, Siti Nur (Journal of Social Science Studies, 2021)
Conflict in the work environment is an unavoidable phenomenon and can have both positive and negative impacts on individuals, teams, and organizations. Well-managed conflict can be a source of innovation and increased teamwork, but if left without proper resolution, it can reduce productivity, increase work stress, and hinder the achievement of organizational goals. This research aims to analyze effective conflict management strategies to create a harmonious work environment and increase employee productivity. Using a literature study approach, this research examines various theories, models, and previous research results regarding conflict resolution techniques in organizations. The analysis shows that conflict management strategies based on open communication, constructive negotiation, and mediation by third parties can help reduce the negative impact of conflict. The development of clear organizational policies regarding conflict handling and the implementation of a work culture that supports collaboration can increase the effectiveness of conflict resolution. The findings of this study confirm that organizations need to take proactive steps to identify, analyze, and resolve conflicts systematically in order to create a conducive and productive work environment. Conflict can be managed into opportunities to strengthen teamwork and improve overall organizational efficiency.